Aproximaciones hegelianas en el marco de la Revolución Francesa - Guerrero Portales, Rudy (2008)
Universal history began for Hegel with “polis greek”, and with it, has arisen for the first time the conscience for freedom, but the french revolution marks a consciously beginning for freedom as soon as it is elevated to right rank. In the case of Germany, people experience a true national collapse with the political and economical disintegration of the contry, and just exactly, the Hegelian philosophy offers a metholology, from the historical point or view, to understand that revolution are organic elements necessary for human evolution.